Repercussions of digital learning on the mental health of students - CIOBICA, Adrian (Acta et Commentationes, Sciences of Education, 2026)
Abstract. The widespread adoption of digital learning environments has created both opportunities and challenges for students’ mental health, highlighting the need for a comprehensive examination of the ways in which technological engagement intersects with cognitive, emotional, and social well-being. While digital education provides unprecedented flexibility, accessibility, and personalized learning pathways, it also introduces risks such as social isolation, digital fatigue, and increased anxiety. This article explores the theoretical foundations of mental health in educational contexts, drawing on frameworks from psychology, pedagogy, and digital learning research to illuminate the mechanisms through which online learning affects students’ cognitive, emotional, and social development. Drawing on empirical research and illustrative case studies, the analysis identifies strategies for fostering resilience, enhancing self-regulation, and designing digital learning environments that reduce mental health risks while promoting engagement and academic performance. The study emphasizes the importance of institutional policies, teacher training, and technology-mediated interventions that prioritize mental health alongside academic outcomes, highlighting that by placing mental health at the center of digital pedagogy, educational technologies support both knowledge acquisition and the development of psychological resilience and holistic student competencies.